Propagação vegetativa e análise da diversidade genética em Eugenia involucrata de candolle (myrtaceae) - Stefanel, Charlene Moro (2020)
Eugenia involucrata is endowed with high economic and environmental potential, however, the recalcitrant seed storage makes it difficult to produce seedlings by sexual way and justify studies related to vegetative propagation. Besides that, the sustainability of natural remnants is under threat due to the increasing fragmentation to which forest ecosystems have been subjected in recent decades. These questions justify studies that provide subsidies for seedling production by vegetative propagation and for the conservation of genetic resources. Thus, the present study aimed to investigate aspects of micropropagation and minicutting techniques, as well as to quantify genetic variability and to analyze the genetic structure of three natural fragments of E. involucrata. Several experiments were performed whereby, first, the antibiotic was analyzed using the method streptomycin sulfate and its effect in vitro control of endogenous bacteria in shoots of E. involucrata. Also, the effect of antioxidant PVP on the nutrient medium ½MS and gibberellic acid (GA3) on in vitro elongation of nodal segments was evaluated. The influence of four colors of Light Emitting Diodes - LEDs (white, blue, red and green) and cold white fluorescent lamps of daylight type were observed in the in vitro culture of E. involucrata. Also, the influence of different concentrations of BAP, IBA, KIN and NAA on in vitro multiplication was analyzed. Also, the effect of PVP and ascorbic acid prior to rooting was evaluated and the effect of IBA on rooting of E. involucrata minicuttings was also analyzed. In addition, experiments were performed to analyze the structure and genetic diversity of three natural E. involucrata fragments using microsatellite markers. Addition of the antibiotic streptomycin sulfate to the ½MS nutrient medium in the absence of prior explant contamination controls the proliferation of bacterial colonies. Moreover, immersion of explants in the antibiotic does not control the proliferation of bacteria. The use of PVP in the nutritional medium ½MS is not necessary. GA3 has a positive effect on in vitro elongation. LEDs lamps have a favorable effect on the in vitro development of the species. BAP, KIN and IBA phytoregulators are dispensable, however, 2µM NAA is important in the in vitro multiplication of E. involucrata shoots. Regarding the propagation of the species via minicutting, there was no effect of antioxidants PVP and ascorbic acid on phenolic oxidation, which even had a reduced average (11.81%). In the subsequent experiment, oxidation was low (18.33%) and rhizogenesis was also very low (1.11%) and unaffected by IBA despite high concentrations (to 10.000mg L-1) of auxin being tested. The E. involucrata fragments analyzed showed high genetic variability, mostly distributed within the remnants themselves, and low genetic differentiation. Regarding the mode of reproduction, they are classified as mixed with predominance of crosses. The set of results obtained may contribute to the continuity of research related to E. involucrata in several areas of knowledge, which had not yet been explored.